Stereotactic Body Radiotherapy for Spinal Metastases: Clinical Experience in 134 Cases From a Single Japanese Institution. (12th October 2018) - Ito, Kei; Ogawa, Hiroaki; Shimizuguchi, Takuya; Nihei, Keiji; Furuya, Tomohisa; Tanaka, Hiroshi; Karasawa, Katsuyuki
Object: This study aimed to clarify the outcomes of stereotactic body radiotherapy for spinal metastases with a uniform dose fractionation schedule in our institution. Materials and Methods: Patients treated with spine stereotactic body radiotherapy were retrospectively reviewed. The prescribed dose was 24 Gy in 2 fractions. End points were local control, pain control, and adverse events. Local control was defined as elimination, shrinkage, or stable disease in the tumor on imaging evaluations. Pain status was measured on a scale of 0 to 10 by patients' self-reports, and pain response was defined as the time at which pain scale score decreased by 2 or more from the baseline score without increase in analgesics. In addition, various treatment- and tumor-specific factors were evaluated to determine predictive values for local and pain control. Results: This study included 134 lesions in 131 patients, with: lesion histopathology, lung/colorectal/thyroid/renal/breast/prostate/sarcoma/other cancer, 24/22/18/14/12/10/6/25; reirradiation stereotactic body radiotherapy, 82 (61.2%) cases; and postoperative stereotactic body radiotherapy for epidural spinal cord compression, 45 (33.6%) cases. Median follow-up after stereotactic body radiotherapy was 9 months. The 1-year local control rate was 72.3%. Seventy (79.5%) of the 88 cases with pain from spinal metastases achieved pain response. The 1-year pain progression-free rate was 61.7%. Regarding metastases from colorectal cancer, local and pain control rates at 1 year were significantly lower compared with other cancer types (local control rate, 34.1% vs 81.8%; P < .01; pain progression-free rate, 36.9% vs 69.9%; P = .02). On multivariate analysis, colorectal cancer metastases and radiation history were identified as independent predictors of lower local and pain control rates. Radiation-induced myelopathy, radiculopathy, and vertebral compression fractures were observed in 0, 2 (1.5%), and 16 (11.9%) cases, respectively. Conclusions: This study showed that spine stereotactic body radiotherapy achieved good local and pain control, with a clinically acceptable safety profile. However, stereotactic body radiotherapy may be less effective against spinal metastases from colorectal cancer.